Transparansi dan Akuntabilitas Dalam Proses Rekapitulasi Suara PILKADA (Pemilihan Kepala Daerah) di KPU Kabupaten Sidoarjo - Wistiaulia, Marcella Eka; Muljanto, Muhammad Agus (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
This study examines the implementation of transparency and accountability in the vote recapitulation process during the 2024 Sidoarjo Regional Election. Transparency was realized through real-time data accessibility using Sirekap Web technology, stakeholder involvement, and openness in each recapitulation stage. Accountability was demonstrated through official reporting, independent supervision by Panwascam, and layered verification mechanisms. The study utilized literature analysis and documentation methods, with data sourced from news outlets and academic literature. The findings indicate that the applied transparency and accountability increased public trust in the election results, despite technical and human resource challenges. The conclusion highlights the importance of technical training and comprehensive evaluation to improve electoral effectiveness. This study also recommends integrating digital technology and oversight mechanisms in future elections.